FcRn-hitchhiking BSA-galactose nanoparticles for liver-targeted delivery of astaxanthin in non-alcoholic fatty liver - Ruojing Liu; Hang Xu; Huihui Wang; Kexin Xia; Shasha Cheng; Yukun Song; Mingqian Tan (Chemical Engineering Journal, 2026)

Astaxanthin-loaded proliposomes as a novel strategy to enhance stability, bioaccessibility, and antioxidant activity - Hang Xu; Zhiwen Lin; Ruojing Liu; Xinyu Guo; Huiling Hao; Shuaiya Liu; Wentao Su; Yukun Song; Mingqian Tan (Food Bioscience, 2026)

A theoretical study on gas-phase reactions of CF3CH=CF2 with OH: mechanism, kinetics and insights - Peng Zhang; Lu Ma; Haomin Wang; Huirong Li; Ruojing Song; Zhiguo Wang; Yuxi Sun; Yunju Zhang (Journal of Fluorine Chemistry, 2023)

CAS FGOALS-g3 Model Datasets for the CMIP6 Scenario Model Intercomparison Project (ScenarioMIP) - Ye Pu; Hongbo Liu; Ruojing Yan; Hao Yang; Kun Xia; Yiyuan Li; Li Dong; Lijuan Li; He Wang; Yan Nie; Mirong Song; Jinbo Xie; et al. (Advances in Atmospheric Sciences, 2020)
This paper describes the datasets from the Scenario Model Intercomparison Project (ScenarioMIP) simulation experiments run with the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System Model, GridPoint version 3 (CAS FGOALS-g3). FGOALS-g3 is driven by eight shared socioeconomic pathways (SSPs) with different sets of future emission, concentration, and land-use scenarios. All Tier 1 and 2 experiments were carried out and were initialized using historical runs. A branch run method was used for the ensemble simulations. Model outputs were three-hourly, six-hourly, daily, and/or monthly mean values for the primary variables of the four component models. An evaluation and analysis of the simulations is also presented. The present results are expected to aid research into future climate change and socio-economic development.